Depth profiling of tribological films by combined ion sputtering and infrared reflection absorption spectroscopy - Sidorenko, Nikolai; Fickenscher, Georg; Hübsch, Robert; Lykhach, Yaroslava; Franke, Jörg W.H.; Fritz, Janine; Merk, Daniel; König, Thomas; Hosenfeldt, Tim; Brummel, Olaf; Libuda, Jörg (Applied Surface Science, 2026)
Tribo-films are nanometer- to micrometer-scale reaction layers formed by tribological processes (friction, wear, lubrication) under boundary lubrication. They play a key role in anti-wear performance, with functionality strongly linked to the presence and distribution of specific chemical groups. Characterizing these features in real components requires advanced spectroscopic methods with high chemical specificity and depth resolution. We present a depth-profiling technique combining infrared reflection–absorption spectroscopy (IRAS) with controlled Ar+ ion sputtering under high or ultra-high vacuum conditions. The method was applied to washers from two axial cylindrical roller bearings that showed distinct wear behaviors in performance tests. It is fully compatible with industrial components and enables direct comparative analysis. Maintaining optical alignment during sputtering yields high signal-to-noise ratios, allowing detection of trace IR-active species down to a few percent of a monolayer. The approach also permits evaluation of film thickness and homogeneity. Most importantly, the combination of depth sensitivity and chemical specificity enables vertical mapping of functional groups and reconstruction of the tribo-film's composition. This IRAS-based method thus provides a powerful tool for studying tribological films and advancing understanding of anti-wear mechanisms under real-world conditions.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Depth-profiling; Infrared reflection absorption spectroscopy; Ion sputtering; Tribo-films; Tribology